Cooperation or confrontation? Public and private governance and smallholders' incomes in the cocoa sector in Ghana and in Côte d'Ivoire - Felix Maile (Südwind-Verlag, 2020)
The production and consumption of raw materials such as coffee, cocoa and cotton have created extensive but unequal links between the Global North and Global South. The structure and governance of these links have changed over time, but have been determined mainly by a few multinational companies since the 1980s. Within global production networks, these companies trade these commodities or process them into intermediate and final products. At the same time, the unequal distribution of value added within the global commodity chains comes to the disadvantage of millions of small farmers in the Global South, whose income depends heavily on these raw materials. They receive only a small share of the value of the end products and their incomes are affected by volatile global prices. In order to counteract this lack of economic sustainability, as well as social and ecological problems in commodity sectors, a large number of private certification initiatives by independent organisations as well as sustainability programmes initiated by multinational companies themselves have emerged in recent years. However, the functioning and effects of these initiatives are not well understood. In his master thesis, Felix Maile takes up these global interrelations and examines the impact of various sustainability initiatives on incomes for cocoa farmers in Ghana and Côte d'Ivoire. Based on interviews with experts from the cocoa sector in Europe, Ghana and Côte d'Ivoire, the author analyses the structure and governance of the global cocoa production network, the price formation in the cocoa sector, and the regulations in the main producing countries in West Africa, which aim to stabilise producer prices and increase productivity. In this context, he shows that there is little cooperation between sustainability initiatives of private companies and public policy measures with regard to producer prices. This can also be explained by the different interests of these actors, as Felix Maile shows with regard to the current debate about a common 'Living Income Differential' in Ghana and Côte d'Ivoire. This paper is an important contribution to the discussion on the unequal distribution of value added and power asymmetries in various commodity sectors. In this context, the interrelation between governmental regulations in producer countries and private sustainability initiatives and the role of governance by different actors are particularly relevant, as these are decisive factors for the development of resource-dependent countries in the Global South.
Keywords: 330